Stress Resilience and the Dynamic Regulation of Glucocorticoids. (5th June 2019) - Vitousek, Maren N; Taff, Conor C; Ryan, Thomas A; Zimmer, Cedric
Abstract: Vertebrates respond to a diversity of stressors by rapidly elevating glucocorticoid (GC) levels. The changes in physiology and behavior triggered by this response can be crucial for surviving a variety of challenges. Yet the same process that is invaluable in coping with immediate threats can also impose substantial damage over time. In addition to the pathological effects of long-term exposure to stress hormones, even relatively brief elevations can impair the expression of a variety of behaviors and physiological processes central to fitness, including sexual behavior, parental behavior, and immune function. Therefore, the ability to rapidly and effectively terminate the short-term response to stress may be fundamental to surviving and reproducing in dynamic environments. Here we review the evidence that variation in the ability to terminate the stress response through negative feedback is an important component of stress coping capacity. We suggest that coping capacity may also be influenced by variation in the dynamic regulation of GCs—specifically, the ability to rapidly turn on and off the stress response. Most tests of the fitness effects of these traits to date have focused on organisms experiencing severe or prolonged stressors. Here we use data collected from a long-term study of tree swallows ( Tachycineta bicolor ) to test whether variation in negative feedback, or other measures of GC regulation, predict components of fitness in non-chronically stressed populations. We find relatively consistent, but generally weak relationships between different fitness components and the strength of negative feedback. Reproductive success was highest in individuals that both mounted a robust stress response and had strong negative feedback. We did not see consistent evidence of a relationship between negative feedback and adult or nestling survival: negative feedback was retained in the best supported models of nestling and adult survival, but in two of three survival-related analyses the intercept-only model received only slightly less support. Both negative feedback and stress-induced GC levels—but not baseline GCs—were individually repeatable. These measures of GC activity did not consistently covary across ages and life history stages, indicating that they are independently regulated. Overall, the patterns seen here are consistent with the predictions that negative feedback—and the dynamic regulation of GCs—are important components of stress coping capacity, but that the fitness benefits of having strong negative feedback during the reproductive period are likely to manifest primarily in individuals exposed to chronic or repeated stressors.